IMPROVEMENT THE CALCULATION OF THE STABILITY OF BUILDING LOCATED NEAR THE SLOPES FOR STRUCTURAL UNSTABLE SOILS - Ivanova, M. S.; Konoval, S. V.; Abed, S. F. (Science and Transport Progress, 2015)
Purpose. This article is devoted to research of soil in complex engineering and geological conditions, as well as ways to improve the stability of the stacked bases structurally unstable soils. The relevance of this work lies in the solution of grounds stability problem interacting with foundations established on structurally unstable soils. In accordance with the researches results compiled recommendations aimed to the improvement of the base stability folded by structurally unstable soils is supposed. Methodology. The aim of the work is to improve the reliability of the strength characteristics obtained by the method of mathematical modeling of the expected processes. The objective was the enhancements the existing testing methods and technologies in order to determine the relative value of safety factor and reliability assessment of the bearing capacity of the base folded structurally unstable soils. Findings. This system was designed to ensure the automated measurement of deformation parameters on the on-line with followed mathematical processing and presentation of data in an accessible form. Thus, the obtained results allow drawing the conclusions about the patterns of structure strain state, as well as predicting its future behavior. It all depended on well-formed mathematical algorithm, which is adjusted by tests conducted in natural conditions in selected regions of the Donbass region. Originality. One of the most effective ways to start and register a timely activation of deformation processes in plant cells from the damaging effects is the use of automated systems with high reliability which receive signals from the deformable objects. The main tool used to solve the problem, was the method of mathematical modeling in ACS reproducing receptive model processes in the soil with a program «HRUNT» and «MONOMAKH». And modeling the three-dimensional base of the building on the joint work of the soil mass and building by the finite element method (FEM-calculation) in the PC-LIRA system. Practical value. The problem of increasing the sustainability of slope, the prognosis of deformations and their strengthening, remains urgent. This is due to the increasing shortage of available land area and the location of facilities in cramped conditions, near the slopes composed of the non-uniform grounds.